Impact of Genotype, Serum Bile Acids, and Surgical Biliary Diversion on Native Liver Survival in FIC1 Deficiency. Issue 2 (13th July 2021) - van Wessel, Daan B.E.; Thompson, Richard J.; Gonzales, Emmanuel; Jankowska, Irena; Shneider, Benjamin L.; Sokal, Etienne; Grammatikopoulos, Tassos; Kadaristiana, Agustina; Jacquemin, Emmanuel; Spraul, Anne; Lipiński, Patryk; Czubkowski, Piotr; et al.
Abstract : Background and Aims: Mutations in ATPase phospholipid transporting 8B1 (ATP8B1) can lead to familial intrahepatic cholestasis type 1 (FIC1) deficiency, or progressive familial intrahepatic cholestasis type 1. The rarity of FIC1 deficiency has largely prevented a detailed analysis of its natural history, effects of predicted protein truncating mutations (PPTMs), and possible associations of serum bile acid (sBA) concentrations and surgical biliary diversion (SBD) with long‐term outcome. We aimed to provide insights by using the largest genetically defined cohort of patients with FIC1 deficiency to date. Approach and Results: This multicenter, combined retrospective and prospective study included 130 patients with compound heterozygous or homozygous predicted pathogenic ATP8B1 variants. Patients were categorized according to the number of PPTMs (i.e., splice site, frameshift due to deletion or insertion, nonsense, duplication), FIC1‐A (n = 67; no PPTMs), FIC1‐B (n = 29; one PPTM), or FIC1‐C (n = 34; two PPTMs). Survival analysis showed an overall native liver survival (NLS) of 44% at age 18 years. NLS was comparable among FIC1‐A, FIC1‐B, and FIC1‐C (% NLS at age 10 years: 67%, 41%, and 59%, respectively; P = 0.12), despite FIC1‐C undergoing SBD less often (% SBD at age 10 years: 65%, 57%, and 45%, respectively; P = 0.03). sBAs at presentation were negatively associated with NLS (NLS at age 10 years, sBAs < 194 µmol/L: 49% vs. sBAs ≥ 194 µmol/L: 15%; P = 0.03). SBD decreased sBAs (230 [125‐282] to 74 [11‐177] μmol/L; P = 0.005). SBD (HR 0.55, 95% CI 0.28‐1.03, P = 0.06) and post‐SBD sBA concentrations < 65 μmol/L ( P = 0.05) tended to be associated with improved NLS. Conclusions: Less than half of patients with FIC1 deficiency reach adulthood with native liver. The number of PPTMs did not associate with the natural history or prognosis of FIC1 deficiency. sBA concentrations at initial presentation and after SBD provide limited prognostic information on long‐term NLS.